2017
DOI: 10.2134/jeq2016.08.0322
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of Onsite Wastewater Treatment Systems on Nitrate Loads Using SWAT in an Urban Watershed of Metropolitan Atlanta

Abstract: Onsite wastewater treatment systems (OWTSs) can be a source of nitrogen (N) pollution in both surface and ground waters. In metropolitan Atlanta, GA, >26% of homes are on OWTSs. In a previous article, we used the Soil Water Assessment Tool to model the effect of OWTSs on stream flow in the Big Haynes Creek Watershed in metropolitan Atlanta. The objective of this study was to estimate the effect of OWTSs, including failing systems, on nitrate as N (NO-N) load in the same watershed. Big Haynes Creek has a draina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
(35 reference statements)
2
2
0
Order By: Relevance
“…According to Jeong et al [11] and Hoghooghi et al [14], the contribution of groundwater to streamflow is relatively high during dry years, similar to the research findings of this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to Jeong et al [11] and Hoghooghi et al [14], the contribution of groundwater to streamflow is relatively high during dry years, similar to the research findings of this study.…”
Section: Discussionsupporting
confidence: 90%
“…By representing the area under the septic system, using available sewer data and TN loads data, a more accurate model of anthropogenic nitrogen inputs into the Hunt River Watershed was able to be developed. This study showed the importance of groundwater contributions to streamflow and nitrogen loading and the findings are corroborated by research conducted by Jeong et al and Hoghooghi et al [11,14]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The average time required for an septic system to malfunction typically is more than 10 years [ 47 ]. Almost 70% of the septic systems that listed as ‘new’ in the original inspection report are more than 10-year old (average = 20 year), which may not have accurately represented the real septic systems condition.…”
Section: Methodsmentioning
confidence: 99%